Use of Therapeutic Plasma Exchange during Extracorporeal Life Support in Critically Ill Cardiac Children with Thrombocytopenia-Associated Multi-Organ Failure - Chong, Mei; Lopez-Magallon, Alejandro J.; Saenz, Lucas; Sharma, Mahesh S.; Althouse, Andrew D.; Morell, Victor O.; Munoz, Ricardo (Frontiers in Pediatrics, 2017)
Background: Thrombocytopenia-associated multi organ failure (TAMOF) in children is a well described factor for increased hospital mortality. Low cardiac output syndrome (LCOS) and the effects of cardiopulmonary bypass (CPB) may manifest with several adverse physiologic and immunologic effects, with varying degrees of thrombocytopenia and multiorgan dysfunction, sometimes very similar to TAMOF. LCOS is a common occurrence in children with critical heart disease, presenting in as much as 23.8% of infants postoperative of congenital heart surgery. Therapeutic plasma exchange (TPE) has been offered as a promising therapy for TAMOF; however, the therapeutic implications of this modality in children with critical heart disease and a clinical diagnosis of TAMOF are unknown. Objectives: We describe our institutional experience with TPE as an adjuvant rescue therapy for children with critical heart disease and a clinical diagnosis of TAMOF, while supported by extracorporeal membrane oxygenation (ECMO). Methods: Single-center retrospective analysis of children with critical heart disease admitted to the CICU and supported by ECMO, undergoing TPE for a clinical diagnosis of TAMOF between January 2006 and June 2015. Results: 41 patients were included for analysis. Median age and weight of patients was 0.6 years (range 0.0-17.2) and 8.5 kg (range 1.5-80.0). TPE was initiated at a median of 1 day (0-13) after initiation of ECMO. Modified organ failure index (MOFI) and platelet count improved after TPE start (p<0.001). Patients with early TPE initiation after ECMO cannulation (<1 day) showed more improvement in MOFI and platelet counts than patients with late TPE initiation (p<0.001 for each). Overall survival to hospital discharge was 53.7%. The within-groups hospital survival was 73.3% for patients with heart failure, 34.8% for patients with congenital heart disease and 100% for those with other cardiac disease (p= 0.016). Conclusion: In children with critical cardiac disease and clinical diagnosis of TAMOF necessitating ECMO for hemodynamic support, concurrent TPE may be associated with an improvement in organ failure and platelet count, particularly when started early. Further studies are warranted to establish the most effective use of TPE and its effect on survival in this population.